Geographical distribution and phenotypic characterization of Malin sheep in three selected states of Peninsular Malaysia - Siti Nabilah Mahdzar; Mohd Aftar Abu Bakar; Nadiatur Akmar Zulkifli; Mahanem Mat Noor; Mohd Hafiz Abdul Rahman; Norfarhan Mohd-Assa’ad; Shairah Abdul Razak (Journal of Animal Science and Technology)
Conservation of indigenous breeds of ruminants is crucial for offering alternatives to commercial breeds. Moreover, it is part of long-term strategies in the agri-food sector to sustain supplies by ensuring genetic resource diversity to overcome climate change and the food crisis. Malin is the only native sheep breed in Malaysia. Due to traits such as heat tolerance and disease resistance, Malin sheep are considered an invaluable biological heritage. However, breeders and industrial producers are not interested in Malin because of their low commercial value and slow growth rate. Hence, this breed is neglected, its population is fragmented, and its numbers are dwindling, without data updates. Therefore, current information regarding Malin sheep is needed, including the latest geographical distribution and phenotypic characterization. First, we determined the population distribution using information from the State Department of Veterinary Services. Data were then collected from 15 studied locations in Pahang, Perak, and Kelantan via purposive sampling. Six qualitative traits and seven morphometric traits were recorded for 152 Malin sheep. These traits were quantitatively analyzed using multi-variate statistical tools to define the best measure to represent body conformation when comparing Malin sheep across studied locations. Findings showed that the Malin Ne population is very small. Morphologically, most Malin sheep exhibit light-brown wool with a course wool type; convex head shape, curved and horned in males but polled in females; and white hoof color. Imputation for missing body weight values in one population was successfully performed based on imputation regression modelling prior to downstream analyses. Kruskal-Wallis tests indicated that the median value of all morphometric traits except female body weight differed significantly between all studied locations. The highest correlation was observed between chest girth and body length in males (ρ=0.76) and chest girth and body weight (ρ=0.76) in females. Non-metric dimensional scaling showed that sheep maintained by smallholders in Pahang and Kelantan are similar phenotypically, but with smaller size compared with Perak. These findings suggest that phenotypic traits can help evaluate and compare sheep body conformation and thus provide an opportunity to distinguish and clarify a herd’s position, thereby highlighting populations requiring management attention.